Seroepidemiology and characterisation of neutralisation escape mutants of enterovirus A71 / Nik Nadia Nik Mohd Nasir - Nik Nadia , Nik Mohd Nasir (2016)
Enterovirus A71 (EV-A71) is an important emerging pathogen causing large epidemics of hand, foot and mouth disease (HFMD) in children. In Malaysia, since its first epidemic in 1997, recurrent cyclical epidemics have occurred every 2-3 years. Currently, no study of the seroepidemiology of EV-A71 infection has been done in Malaysia. The objectives of the current study were to determine the seroepidemiology of EV-A71 infection in children up to 12 years of age, and general urban and rural populations in Malaysia; to identify risk factors for seropositivity to EV-A71 in the rural population; and to generate EV-A71 neutralisation escape mutants to identify neutralisation epitopes. Neutralisation assay was performed to measure the neutralising antibody titres in 2141 serum samples from children, 460 samples from an urban Kuala Lumpur population, and 298 samples from rural Orang Asli populations. A significant association between subjects’ age and seropositivity to EV-A71 was found among the children. Overall, EV-A71 seroprevalence rate and geometric mean titre (GMT) were significantly higher in the 7-12 years age group compared to the 1-6 years age group, and also in epidemic years (1997, 2000, 2003, 2006, 2008/2009, 2012) compared to non-epidemic years. The HFMD incidence rate was highest in children <2 years old. In the population study involving serum samples from healthy individuals aged 1-85 and 1-90 years old for urban and rural populations, respectively, EV-A71 seropositivity was strongly associated with increasing age in both populations. Potential risk factors associated with EV-A71 seropositivity were determined for the rural Orang Asli populations. Orang Asli children ≤12 years had significantly higher EV-A71 seropositivity rates than urban Kuala Lumpur children, and also higher rates in the age groups of 1-3, 4-6 and 7-12 years. Multivariate analysis confirmed that age ≤12 years and using untreated water were independently associated with EV-A71 seropositivity in the Orang Asli population. Lastly, as neutralising antibodies confer protection against iv EV-A71 infection, more studies are needed to discover more neutralisation epitopes. EV-A71 neutralisation escape mutants were generated in vitro by exposing the virus to antibody pressure using a mouse monoclonal antibody (MAB979) for four passages. The amino acid changes were determined by sequencing. Two mutations were detected in the capsid protein of EV-A71 neutralisation escape mutants; threonine to isoleucine, located at the amino acid position 141 on VP2; and aspartic acid to asparagine, located at amino acid position 14 on VP1. Neutralising activity of the EV-A71 escape mutants was tested against EV-A71 monoclonal antibody MAB979, anti-EV-A71 positive mouse sera and human sera. The characterisation of the neutralisation escape mutants suggests that the neutralisation epitopes in humans and animals could be different. In summary, this first EV-A71 seroepidemiology study in Malaysia revealed that young age, using untreated water, and living within rural populations are risk factors associated with EV-A71 infection. The discovered neutralisation epitopes may contribute to development of vaccines or monoclonal antibody therapy.